Look good when you're googled: creating and optimizing your digital identity. Issue 9 (28th October 2014) - Izenstark, Amanda
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to describe techniques librarians can use to enhance their online presence, so that students, patrons, researchers and prospective employers can locate them easily. It is an extension of a presentation given at the Association of College and Research Libraries New England Chapter Annual Conference held in Worcester, MA on May 9, 2014. Design/methodology/approach – The presentation focused on a number of established and emerging tools to share professional contact information and professional output, such as Google, Google+, Twitter, LinkedIn, SlideShare and ImpactStory, among others. Findings – The audience of library faculty and staff from across the Northeastern USA examined the results that appeared when they searched for themselves in major search engines (Google, Bing and DuckDuckGo) and learned strategies and tools for optimizing the results that come up when others search for their contact information. Practical implications – Librarians who focus on enhancing their professional profiles online make it easier for constituents to get assistance with research questions, they can make their value and the institution's value more visible, and facilitate the sharing of information in a field that looks to other institutions and individuals for inspiration for new programs and innovations. Originality/value – While many of these tools are used in the business world to build and cultivate networks and seek employment, even steadily employed librarians can use these tools to make their expertise available to researchers at their institutions and beyond.